The proportion of Hypothyroid in Type 2 Diabetes Mellitus Patients in Dr. Hasan Sadikin Hospital - Armina Latifah; Nina Tristina; Fajar Wasilah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Type 2 Diabetes Mellitus (T2DM) and thyroid dysfunction often coexist. Both diseases have overlapping pathomechanisms and increased risk along with advanced age. The prevalence of hypothyroidism in patients with T2DM is 12%-15% compared to 1.3%-4.6% of the general population. Glycemic control is an essential factor in developing hypothyroidism. Thyroid Stimulating Hormone (TSH) levels are used to diagnose hypothyroidism because subclinical hypothyroidism commonly shows normal T4 and T3 levels. This study aimed to measure TSH levels in patients with T2DM. The study design was observational, descriptive, and cross-sectional. Researchers carried out TSH measurements by using leftover samples from T2DM patients. Subjects were recruited by consecutive sampling. The inclusion criteria were subjects > 35 years old who were diagnosed with T2DM. The exclusion criteria were subjects who were previously diagnosed with hyperthyroidism or hypothyroidism. This study found that 11% of 71 subjects had elevated TSH levels. The subjects were 32 (45%) male and 39 (55%) female patients aged 38-72 years. Subjects with high TSH levels were between the ages of 49 and 72. There were 5 of 8 subjects (62.5%) with elevated TSH levels and poor glycemic control. The prevalence of hypothyroidism in T2DM was 11%. Thyroid stimulating hormone is recommended for T2DM, especially in patients over 50 with poor glycemic control.